Role of Reactive Oxygen Species in Aging and Age-Related Diseases: A Review - Anik, Muzahidul I.; Mahmud, Niaz; Masud, Abdullah Al; Khan, Md Ishak; Islam, Md Nurul; Uddin, Shihab; Hossain, M. Khalid (ACS applied bio materials, 2022)
Research on the role of reactive oxygen species (ROS) in the aging process has advanced significantly over the last two decades. In light of recent findings, ROS takes part in the aging process of cells along with contributing to various physiological signaling pathways. Antioxidants being cells’ natural defense mechanism against ROS-mediated alteration, play an imperative role to maintain intracellular ROS homeostasis. Although the complete understanding of the ROS regulated aging process is yet to be fully comprehended, current insights into various sources of cellular ROS and their correlation with the aging process and age-related diseases are portrayed in this review. In addition, results on the effect of antioxidants on ROS homeostasis and the aging process as well as their advances in clinical trials are also discussed in detail. The future perspective in ROS-antioxidant dynamics on antiaging research is also marshaled to provide future directions for ROS-mediated antiaging research fields.